Strengthening Institutional Social-Economic Institutions Through Village-Owned Enterprises (BUMDes) - Niken Widyastuti; Diana Anggraini Kusumawati (AIBPM Publisher, 2024)
Potential in the area, including institutions, people, and natural resources, should be handled, one of which is Village-Owned Enterprises (BUMDes). The performance of BUMDes must considerably enhance the welfare of the populace. Under BUMDes' work system, all commercial and community economic activities are facilitated in a professionally managed institution or corporate organization. As a consequence, community companies are successful and fruitful, enabling the best possible management of all village economic endeavors. The purpose of this study is to determine the reinforcement of local socio-economic institutions in Pagerharjo, Samigaluh District, Kulon Progo Regency through BUMDes. The research employs a qualitative descriptive methodology, with findings that highlight the significance of generalization. In an attempt to fully realize the village's potential, BUMDes Binangun Pagerharjo Village has developed into an organization that is capable of boosting the local economy through the establishment of social services, economic business development, and BUMDes institutional strengthening initiatives. BUMDes Pagerharjo can create jobs, boost local revenue, and bolster the local economy by empowering the people and opening up business options.